Fulminant sepsis post splenectomy. Report of a case and review of the literature - Novoa-Millones, Luis (2020)
This is the case of a 37-year-old male patient who was admitted to emergency ward for widespread purplish lesions and a history of being splenectomized 20 years ago. He quickly progressed to distributive shock, respiratory failure, multiorgan failure, DIC and death. The final diagnosis was purpura fulminans (PF) secondary to fulminant post-splenectomy sepsis by bacteriemia due to Streptococcus pneumoniae. Related concepts and the role of spleen in responding to infections by encapsulated bacteria are reviewed.